The Activation and Signaling Mechanisms of GPR56/ADGRG1 in Melanoma Cell - Huang, Kuan-Yeh; Lin, Hsi-Hsien (Frontiers in Oncology, 2018)
Adhesion G protein-coupled receptors (aGPCRs) constitute the second largest GPCR subfamily. GPR56/ADGRG1 is a member of the ADGRG subgroup of aGPCRs. Although GPR56 is best known for its pivotal role in the cerebral cortical development, it is also important for tumor progression. Numerous studies have revealed that GPR56 is expressed in various cancer types with a role in cancer cell adhesion, migration and metastasis. In a recent study, we found that the immobilized GPR56-specific CG4 antibody enhanced IL-6 production and migration ability of melanoma cells. In this review, we will summarize the current understanding of GPR56 function and discuss the activation and signaling mechanisms of GPR56 in melanoma cells.